A review with updated perspectives on in vitro and in vivo wound healing models - Sarian, Murni Nazira; Zulkefli, Nabilah; Zain, Shazeli; Maniam, Sandra; Fakurazi, Sharida (The Scientific and Technological Research Council of Tuerkiye - Tubitak,turkiye Bilimsel Ve Teknik Arastirma Kurumu, 2023)
A skin wound or perforation triggers a series of homeostatic reactions to safeguard internal organs from invasion by pathogens or other substances that could damage body tissues. An injury may occasionally heal quickly, leading to the closure of the skins structure. Healing from chronic wounds takes a long time. Although many treatment options are available to manage wound healing, an unmet therapy need remains because of the complexity of the processes and the other factors involved. It is crucial to conduct consistent research on novel therapeutic approaches to find an effective healing agent. Therefore, this work aims to cover various in vitro and in vivo methodologies that could be utilised to examine wound recovery. Before deciding on the optimal course of action, several techniques' benefits, drawbacks, and factors need to be reviewed.